Profiling the Expression of Circulating Acute-Phase Proteins, Cytokines, and Checkpoint Proteins in Patients with Severe Trauma: A Pilot Study - Wu SC; Rau CS; Kuo PJ; Shih FY; Lin HP; Wu YC; Hsieh TM; Liu HT; Hsieh CH (Dove Medical Press, 2021)
Shao-Chun Wu,1,* Cheng-Shyuan Rau,2,* Pao-Jen Kuo,3 Fu-Yuan Shih,2 Hui-Ping Lin,3 Yi-Chan Wu,3 Ting-Min Hsieh,4 Hang-Tsung Liu,4 Ching-Hua Hsieh3 1Department of Anesthesiology, Kaohsiung Chang Gung Memorial Hospital and Chang Gung University College of Medicine, Kaohsiung, Taiwan; 2Department of Neurosurgery, Kaohsiung Chang Gung Memorial Hospital and Chang Gung University College of Medicine, Kaohsiung, Taiwan; 3Department of Plastic Surgery, Kaohsiung Chang Gung Memorial Hospital and Chang Gung University College of Medicine, Kaohsiung, Taiwan; 4Department of Trauma Surgery, Kaohsiung Chang Gung Memorial Hospital and Chang Gung University College of Medicine, Kaohsiung, Taiwan*These authors contributed equally to this workCorrespondence: Ching-Hua HsiehDepartment of Plastic Surgery, Kaohsiung Chang Gung Memorial Hospital and Chang Gung University College of Medicine, No. 123, Ta-Pei Road, Niao-Song District, Kaohsiung, 833, TaiwanTel +886-7-7327476Fax +886-7-3450431Email m93chinghua@gmail.comPurpose: Severe trauma may lead to the systemic release of inflammatory mediators into the circulation with profound acute-phase responses; however, the understanding of the expression of these mediators remains limited. This study aimed to characterize the alterations in the expression of circulating acute-phase proteins, cytokines, and checkpoint proteins in patients with severe trauma injuries.Patients and Methods: The study population included trauma patients in the intensive care unit (ICU) with an injury severity score equal to or greater than 16 and who had used a ventilator for 48 hours. A total of 12 female and 28 male patients were recruited for the study; six patients died and 34 survived. Blood samples collected at acute stages were compared with those drawn at the subacute stage, the time when the patients were discharged from the ICU, or before the discharge of the patients from the hospital.Results: The study identified that the expression of acute-phase proteins, such as alpha-1-acid glycoprotein and C-reactive protein, and cytokines, including granulocyte colony-stimulating factor, interleukin-6, and interleukin-1 receptor antagonist, was elevated in the circulation after severe trauma. In contrast, the levels of acute-phase proteins, such as alpha-2-macroglobulin, serum amyloid P, and von Willebrand factor, and cytokines, including interleukin-4 and interferon gamma-induced protein 10, were reduced. However, there were no significant differences in the expression of checkpoint proteins in the circulation.Conclusion: The dysregulated proteins identified in this study may serve as potential therapeutic targets or biomarkers for treating patients with severe trauma. However, the related biological functions of these dysregulated factors require further investigation to validate their functions.Keywords: circulation, inflammatory reaction, biomarkers, severe trauma, critical illness